The Assessing the Effectiveness of Digital Media Used by the Directorate General of Taxes to Enhance Tax Literacy among Millennial Taxpayers - Marsela Nur Cahyani; Yuni Fitriyani; Iin Indarti; Triani; Nurdhiana (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the effectiveness of digital media utilization by the Directorate General of Taxes (DGT) in enhancing tax literacy among millennial taxpayers. With the advancement of information technology and the growing dominance of millennials as a significant portion of the taxpayer base, the DGT is required to adopt more modern and adaptive communication strategies. This research employs a quantitative approach by distributing questionnaires to 150 millennial taxpayers who are active on social media and exposed to tax education content from the DGT. The findings indicate that the use of digital platforms such as Instagram, YouTube, and TikTok significantly improves millennials' understanding of their tax obligations, although the effectiveness is still influenced by the intensity and quality of the content delivered. These results suggest that the DGT needs to further optimize its digital communication strategies to ensure greater relevance and engagement among the millennial generation.